2012
DOI: 10.4161/viru.21972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient deprivation on the susceptibility ofGalleria mellonellalarvae to infection

Abstract: Larvae of Galleria mellonella are widely used to study the virulence of microbial pathogens and for assessing the potency of antimicrobial agents. This work examined the effect of nutritional deprivation on the ability of larvae to withstand infection in order to establish standardized conditions for the treatment of larvae for in vivo testing. Larvae deprived of food for seven days demonstrated an increased susceptibility to infection by the yeast Candida albicans. These larvae displayed a lower density of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 32 publications
3
57
0
2
Order By: Relevance
“…Hemocyte depletion has previously been correlated with insect mortality in infection 3,52 , although recent results suggest that this picture is more complex than first belived 37 . Recently, it has been shown that starvation of larvae leads to increased susceptibility to infection through a suppression of immune responses 53 . In the assays described here, larvae were not fed for the duration of the study and it is not known how well fed larvae would respond to L. pneumophila infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hemocyte depletion has previously been correlated with insect mortality in infection 3,52 , although recent results suggest that this picture is more complex than first belived 37 . Recently, it has been shown that starvation of larvae leads to increased susceptibility to infection through a suppression of immune responses 53 . In the assays described here, larvae were not fed for the duration of the study and it is not known how well fed larvae would respond to L. pneumophila infection.…”
Section: Discussionmentioning
confidence: 99%
“…G. mellonella larvae were acquired from Alcotán Valencia SLU and kept at 21°C in darkness with a nonrestricted diet. It has been reported that food deprivation of G. mellonella larvae leads to reductions in cellular and immune responses (38). Larvae were used within 12 Infection of G. mellonella larvae.…”
Section: Methodsmentioning
confidence: 99%
“…G. mellonella is an established and powerful model for the investigation of gut microbe homeostasis and foodborne diseases. [14][15][16] This species is also being investigated as a source for novel anti-infectives 17 and the availability of a comprehensive transcriptome allows the detailed molecular analysis of its immune response by transcriptional profiling and mass spectrometry. 18 We added bacteria to the G. mellonella larval diet to experimentally mimic the most common routes of natural exposure to microbes.…”
Section: Introductionmentioning
confidence: 99%